Cl-/HCO3- exchanger slc26a6: a pH regulator shapes the cardiac action potential - Aiello, Ernesto Alejandro (2017)
Regulation of intracellular pH (pHi) is often considered a housekeeping function, contributing little to cardiac contractile activity. With the study published by Sirish et al. in this issue of Circulation: Arrhythmia and Electrophysiology, a Cl-/HCO3- exchanger is revealed to have a more central role in the heart.